What’s the use of being nice? Characteristics of feedback comments that students intend to use in improving their work - David Playfoot (Assessment and Evaluation in Higher Education, 2024)
Although teachers spend a lot of time striving to provide high-quality feedback, students do not always act upon it and may rate it as unhelpful. The current study attempted to determine the characteristics of feedback that influence students’ intentions to use teachers’ comments in their future work. Participants rated real feedback comments for clarity, tone and encouragement as well as their intention to use those comments if they had received them on their own work in three studies. Multiple regression analyses demonstrated that intention to use ratings were higher for comments which were ‘nice’ (supportive, encouraging, motivating, positive in tone) and ‘usable’ (clear, constructive, helpful). We argue that these data provide clear guidance for instructors as to how to approach the provision of written feedback on student work.